Transformation of Alcohol Dehydrogenase1 in Tomato - Tan, Xue Hui (Universiti Malaysia Sarawak, UNIMAS, 2013)
Alcohol dehydrogenase (Adh) is a versatile enzyme that contributes to biological pathways in plants such as germination, fermentation, stress tolerance in stresses like osmotic, oxygen and wound. It catalyzes the interconversion of alcohols, aldehyde and ketone. Previous works have detected the presence of Adh in sago palm, and subsequently isolated and characterised the gene. The objective of this study is to study the expression of Adh1 in tomato. Adh1 gene is studied with transformation into tomato plants using Agrobacterium-mediated transformation with Agrobacterium tumefaciens. Seeds of tomatoes were transformed with A.tumefaciens strain LBA4404 carrying the pGSA1131 binary vector. Transformants were confirmed using polymerase chain reaction (PCR). Confirmation with PCR is done with the use of specific primers for Adh1 gene. DNA fragments of 1.1 kb were successfully amplified with the use of Nco1 and BamH1 primers from total DNA of transgenic plants. Reconfirmation tests with similar primers and bar primers were run to reconfirm the insert. There were total 16 transformants being analysed with 13 successfully transformed.